P36 Block of interferon γ and co-culture with smDCs enhance antigen-specific T-reg suppression ability in autoimmune hepatitis type 2. (16th November 2010) - Longhi, M S; Mieli-Vergani, G; Ma, Y; Vergani, D
Abstract : Introduction: CD4posCD25high regulatory T-cells (T-regs), central to immune homeostasis, are impaired in autoimmune hepatitis type 2 (AIH-2), a severe disease often leading to end-stage liver damage despite immunosuppression. T-regs specific for cytochrome P450IID6 (CYP2D6), the target autoantigen in AIH-2, can be expanded in vitro and exert a stronger suppressor function over damaging effector T-cells than non antigen-specific T-regs. Aim: To explore the mechanisms controlling antigen-specific T-reg suppressor function in AIH-2. Method: 13 AIH-2 patients positive for the HLA-DR7 and DR3 predisposing MHC alleles, were studied. Peptide-pulsed semi-mature dendritic cells (smDCs) were obtained from CD14pos cells following treatment with IL-4, GM-CSF, interferon-λ and CYP2D6 peptides. CYP2D6-T-regs were obtained after CD4posCD25high cell purification from CD14neg cells cultured for 8 days in presence of CYP2D6 peptide, high dose interleukin-2 (IL-2) and T-cell expander. Frequency of interferon (IFN)-γ, IL-2, IL-17, IL-4, IL-10 and TGF-β producing cells within CYP2D6-T-regs was tested before and after 2-day co-culture with smDCs (smDC-CYP2D6-T-regs) by intracellular staining; suppressor function was determined by proliferation assay after T-reg addition to CD25neg target cells. Results: There was no difference in the frequency of IL-2, IL-17, IL-4, IL-10 and TGF-β producing CYP2D6-T-regs in the absence or presence of smDCs, while IFN-γ-producing cells were more frequent in the absence of smDCs (1.39±0.3 vs 0.4±0.1; p=0.046). Treatment with anti-IFN-γ neutralising antibody decreased the frequency of IFN-γ-producing cells within CYP2D6-T-regs to 0.46±0.2 (p=0.041) and enhanced their suppressor function over CD25neg cell proliferation from 23% to 45.6% (p=0.04), this value being similar to that obtained after adding smDC-CYP2D6-T-regs (50%). As engagement of the signalling molecule B7-H1 on smDCs inhibits IFN-γ secretion, we tested whether its blockage affects the number of IFN-γ-producing cells and/or smDC-CYP2D6-T-reg suppressor function. Interestingly, blockage of B7-H1 did not affect smDC-T-regs ability to suppress despite incrementing the frequency of IFN-γ-producing cells (1.63±0.08; p<0.001), suggesting that smDCs enhance antigen-specific T-reg function independently of IFN-γ. Conclusion: In AIH-2 T-reg suppression ability is enhanced by control of IFN-γ production and by co-culture with peptide-pulsed smDCs. These manoeuvres should be considered to obtain highly potent clinical-grade T-regs for immunotherapy. The mechanism through which smDCs augment suppression remains to be clarified.